THE INFLUENCE OF DISCIPLINE ON THE OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION IN ELEMENTARY SCHOOL STUDENTS - Rahim, Abdul; Madi; Jufri; Maudin (JEC (Jurnal Edukasi Cendekia), 2024)
Discipline plays a very important role in improving the learning outcomes of Islamic Religious Education (PAI) in elementary school students. With a disciplined attitude, students can be more focused in understanding the material, carrying out worship in an orderly manner, and applying Islamic values. The purpose of this study was to determine the influence of discipline on the learning outcomes of Islamic Religious Education in grade IV students of Elementary School 1 Topa. This type of research is a correlation study aimed at finding out whether or not there is a relationship and if there is some close relationship and whether or not the relationship is meaningful. The approach used is descriptive quantitative where data collection uses research instruments, namely questionnaires and documentation. The results of the study showed that the data met the assumptions of normality and homogeneity, so that regression analysis could be carried out validly. Although there is a fairly strong relationship between discipline and learning outcomes of Islamic Religious Education (PAI), the results of the regression test showed that the influence of discipline was not significant. This indicates that other factors outside of discipline may play a greater role in determining student learning outcomes.